Phosphorus acquisition by citrate‐ and phytase‐exuding Nicotiana tabacum plant mixtures depends on soil phosphorus availability and root intermingling. Issue 3 (17th July 2018) - Giles, Courtney D.; Richardson, Alan E.; Cade‐Menun, Barbara J.; Mezeli, Malika M.; Brown, Lawrie K.; Menezes‐Blackburn, Daniel; Darch, Tegan; Blackwell, Martin S.A.; Shand, Charles A.; Stutter, Marc I.; Wendler, Renate; Cooper, Patricia; et al.
Abstract : Citrate and phytase root exudates contribute to improved phosphorus (P) acquisition efficiency in Nicotiana tabacum (tobacco) when both exudates are produced in a P‐deficient soil. To test the importance of root intermingling in the interaction of citrate and phytase exudates, Nicotiana tabacum plant‐lines with constitutive expression of heterologous citrate (Cit) or fungal phytase (Phy) exudation traits were grown under two root treatments (roots separated or intermingled) and in two soils with contrasting soil P availability. Complementarity of plant mixtures varying in citrate efflux rate and mobility of the expressed phytase in soil was determined based on plant biomass and P accumulation. Soil P composition was evaluated using solution 31 P NMR spectroscopy. In the soil with limited available P, positive complementarity occurred in Cit + Phy mixtures with roots intermingled. Root separation eliminated positive interactions in mixtures expressing the less mobile phytase ( Aspergillus niger PhyA ) whereas positive complementarity persisted in mixtures that expressed the more mobile phytase ( Peniophora lycii PhyA ). Soils from Cit + Phy mixtures contained less inorganic P and more organic P compared to monocultures. Exudate‐specific strategies for the acquisition of soil P were most effective in P‐limited soil and depended on citrate efflux rate and the relative mobility of the expressed phytase in soil. Plant growth and soil P utilization in plant systems with complementary exudation strategies are expected to be greatest where exudates persist in soil and are expressed synchronously in space and time.